DIPLOMASI KEBUDAYAAN JEPANG TERHADAP INDONESIA DALAM KERANGKA JAPAN-INDONESIA PARTNERSHIP AGREEMENT TAHUN 2012-2015 - Aldrian "; Saiman Pakpahan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research describes the culture diplomacy of Japan toward Indonesia in Japan Indonesia Partnership Agreement in 2012-2015. Culture diplomacy in Japan that was famous in world are cosplay and pop culture. Japan was held World Cosplay Summit in 2000 to another state that have purspose to known the japans culture to the world.The research method used was a qualitative with descriptive as a technic of the research. Writer collects data from books, encyclopedia, journal, mass media and websites to analyze the culture diplomacy of Japan toward Indonesia in Japan Indonesia Partnership Agreement. The theories applied in this research are realism perspective with culture diplomacy theory.The conclusion research about the culture diplomacy of Japan toward Indonesia in Japan Indonesia Partnership Agreement are was done by Japan with held of World Costplay Summit event in 2014, increase of investation of japans culinary in Indonesia and also make culture of Japans was famous in Indonesia..Key words: culture, diplomacy, partnership and agreement.